Analisis Kesadaran Mahasiswa Terhadap Bahaya Cybercrime Di Media Sosial - Irvan Hadi Ramadhan; Erna Kumalasari Nurnawati (STMIK Pringsewu, 2023)
Students are one of the largest users of technology and the internet in Indonesia. This is due to the need for technology and the internet to support the continuity of lectures. On the other hand, students also have the potential to become victims of cybercrime. This is due to a lack of education about the dangers of crime on the internet. In addition, the level of concern for securing themselves in the internet world is still low. Cybercrimes that are rife in Indonesia include identity theft, online fraud, bullying, and others. Even though many cybercrimes occur, it is not uncommon for many users to publish their identities and the locations they are currently visiting via social media. On the other hand, the internet network is very well documented by students, this makes students often use free wifi which is not safe so it is at risk of cybercrime. Cybercrime will not occur if users have the knowledge, to be vigilant, especially students who should understand more about the negative effects of social media. Thus it is necessary to carry out an analysis related to user awareness on social media. This research was conducted on 100 student respondents from the Institut Sains & Teknologi AKPRIND Yogyakarta to find out how much the level of awareness and vigilance regarding the dangers of cybercrime is based on the categories of social media awareness, awareness of using e-mail and awareness of crime on the internet. This is evidenced by the results of the average level of awareness of IST Akprind students in using social media, which is included in the high category, which is as much as 82%. On the other hand, awareness of using e-mail and internet crimes is included in the sufficient category, namely 57.5% and 61.5% respectively. Therefore, assistance, education, or socialization is needed from the Institutions, Faculties, and study programs for students who do not have good awareness. This is because there are still students who do not have good vigilance when using e-mail and the internet.